PENGARUH PERTAMBAHAN BEBAN TERHADAP KESTABILAN TEGANGAN DALAM PEMODELAN PEMBANGKIT LISTRIK TENAGA ANGIN - Evtaleny R Mauboy (Jurnal Media Elektro, 2021)
Voltage stability is the main focus in supplying the electricity power to the consumer. The power quality is important as the stability and the continuing supply is well maintained. This research aims to regulate the system voltage when the load increased with the addition of wind turbines. The simulation using Simulink/MATLAB with 2x1,5MW wind turbines connected to 2 MVA Synchronous Machine. The load is connected and increased gradually. The voltage stability can be maintained when the load is increased up to 50%. The voltage loses its stability when the load near its full capacity. The control is applied and the voltage can be maintained its stability with the addition of reactive power compensation